70Autonomic dysfunction in atrial fibrillation (AF) patients: absent vasomotor reflex to decreased cardiac venous return during af in comparison to sinus rhythm; implications for earlier rhythm control. (18th June 2020) - Malik, V; Mishima, R; Elliott, A; Emami, M; Roberts-Thompson, K; Mahajan, R; Arnolda, L F; Lau, D H; Sanders, P
Abstract: Funding Acknowledgements: Dr Malik is supported by an Australian Postgraduate Award Scholarship from the University of Adelaide. OnBehalf: Centre for Heart Rhythm Disorders, University of Adelaide & Royal Adelaide Hospital Background: A bi-directional relationship exists between AF and the autonomic nervous system (ANS). Patients with AF studied in sinus rhythm (SR) have impaired vasomotor responses to decreased cardiac volume. Whether autonomic dysfunction worsens during AF itself, is unknown.  Purpose: We examined haemodynamic responses to lower body negative pressure (LBNP) in patients with persistent AF compared to AF studied in SR. LBNP decreases cardiac volume, deactivates atrial stretch receptors and induces a reflex to maintain blood pressure by increasing systemic vascular resistance (SVR).  Methods: 21 consecutive patients with paroxysmal or persistent AF were studied; during AF (n = 8) or SR (n = 13). Anti-arrhythmic and anti-hypertensives were withheld for 5 half-lives. Patients underwent LBNP using a custom-made chamber sealing both lower limbs. Negative pressure at sham (-0 mmHg), low (-20 mmHg) and high level (-40 mmHg) was applied for 5 minutes each. Finger photo plethysmography was used for beat-beat-blood pressure. Computation of SVR during AF is not feasible with this method. Therefore, the right forearm was used to perform venous occlusion plethysmography (VOP); non-invasive, well validated with LBNP and impervious to AF: to estimate forearm blood flow (FBF) and SVR (inversely proportional).  Results: Baseline characteristics and responses to LBNP are presented in Table 1. MAP was maintained, and HR rose slightly, in the SR group. MAP and HR decreased in the AF group. VOP demonstrates a reduction in FBF in the SR group (vasoconstriction); whereas the vasomotor response to LBNP was absent during AF. Figure 1 (Panels A-C).  Conclusion: The presence of AF is associated with autonomic dysfunction from impaired cardiac volume regulation. This novel finding may contribute to the known risk of falls and syncope due to AF. Further studies are needed to evaluate whether abnormal cardiac reflexes are involved in atrial remodelling and AF progression.